2017
DOI: 10.1016/j.metabol.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolic profiling of T cells from patients with relapsing-remitting multiple sclerosis reveals an impairment in glycolysis and mitochondrial respiration

Abstract: BackgroundMetabolic reprogramming is shaped to support specific cell functions since cellular metabolism controls the final outcome of immune response. Multiple sclerosis (MS) is an autoimmune disease resulting from loss of immune tolerance against central nervous system (CNS) myelin. Metabolic alterations of T cells occurring during MS are not yet well understood and their studies could have relevance in the comprehension of the pathogenetic events leading to loss of immune tolerance to self and to develop no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 37 publications
3
55
1
Order By: Relevance
“…The increased glucose metabolism after inhibition of miR‐31‐5p in human CD4 + T cells is in accordance with reports of increased glycolysis in immune cells from SLE patients and mouse models of lupus . Furthermore, IFNβ treatment of RRMS patients has been reported to restore the reduced levels of glycolysis in patient T cells . In all, our results indicate that miR‐31‐5p is regulator of T‐cell energy metabolism during type I IFN responses.…”
Section: Discussionsupporting
confidence: 91%
“…The increased glucose metabolism after inhibition of miR‐31‐5p in human CD4 + T cells is in accordance with reports of increased glycolysis in immune cells from SLE patients and mouse models of lupus . Furthermore, IFNβ treatment of RRMS patients has been reported to restore the reduced levels of glycolysis in patient T cells . In all, our results indicate that miR‐31‐5p is regulator of T‐cell energy metabolism during type I IFN responses.…”
Section: Discussionsupporting
confidence: 91%
“…Several researchers have studied the effects of IFN-β treatment either on peripheral nTreg or iTreg [9][10][11][12][13][14][15], but no previous study has investigated the modulation of nTreg and their subsets, Tr1 and Tr1-like cells in the same cohort of patients. Most reports on Treg are based on cross-sectional studies and limited by selection bias, such as a small number of included patients and a short follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…The deletion of autoreactive lymphocytes is normally mediated by apoptosis, however, an escape from mitochondria-mediated apoptosis has been reported in lymphocytes of MS patients [12]. Mitochondria from MS lymphocytes also show a decrease of mitochondrial respiration [13] associated with a specific decrease of complex I and complex IV activities [28], and, of note, mitochondria have been found to range in shape and size and showed thickened cristae [29]. Mitochondrial dependent apoptosis is also depending on mitochondrial respiration, shape and structure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that deletion of autoreactive lymphocytes by apoptosis is defective in patients with MS, thereby permitting these cells to perpetuate a continuous cycle of inflammation within the CNS [10,11]. In particular, the impairment of mitochondria-mediated apoptosis in Cd4+ T lymphocytes [12], as well as, a reduction of mitochondrial respiration are reported in MS patients [13]. Mitochondria have a main role in both cell death and life and they are a major source of reactive oxygen species (ROS) production.…”
Section: Introductionmentioning
confidence: 99%